Redesain Taman Kota Trunojoyo Kota Malang Melalui Pendekatan Lanskap Kota - Irawan Setyabudi; Viktor Tharigas Sianus Agus (http://arl.faperta.ipb.ac.id/, 2020)
Malang City has a number of tourism potentials that can attract tourists. The location of Malang City is very strategic because it is in a highland and has a comfortable temperature. The existence of Malang City is very strategic because access to and tourist attractions in Malang City is very easy, one of which is via train. Malang City has various potential natural, man-made, and indigenous landscapes. Natural resources and unique culture of the community need to be maintained and preserved. One of them is the Trunojoyo City park which is located in front of the entrance or the entrance gate for tourists from the New Station of Malang City. For that, it is necessary to evaluate the characteristics of the city of Malang so that it can support a positive destination image regarding the city of Malang as a tourist destination. The problems in the research location, apart from the unorganized condition of the park, also the lack of a strong character as a city identity, the lack of public appreciation of the existence of city parks. The main function of several parks is not yet clear and is not yet supported by landscape elements that are able to accommodate the activities of its users. This study aims to redesign Trunojoyo City Park, Malang City, so that it can be developed as an ideal and sustainable New City Park. The resulting output is in the form of site plans, cutout drawings, and detailed drawings. While the method used to analyze is descriptive qualitative by referring to the Judge design process (2018). The results of this study indicate that the Trunojoyo city park is not suitable and does not meet the existing standards on the carrying capacity of the park so that a park design recommendation must be provided.